Bulk and surface properties of metal carbides: implications for catalysis. Issue 10 (20th February 2018) - Quesne, Matthew G.; Roldan, Alberto; de Leeuw, Nora H.; Catlow, C. Richard A.
Abstract : We present a comprehensive study of the bulk and surface properties of transition metal carbides with rock salt structures and discuss their formation energies, electronic structure and potential catalytic activity. Abstract : We present a comprehensive study of the bulk and surface properties of transition metal carbides with rock salt structures and discuss their formation energies and electronic structures. The bonding character of the materials is shown to be dependent on the periodic position of the transition metal as well as the surface termination, which in turn tunes the densities of states and electronic surface properties. Specific focus is given to the possible catalytic implications of the surface properties on CO2 hydrogenation.